Juvenile delinquency in a diverse society - Bates, Kristin A. (SAGE, 2021)
Thinking about juvenile delinquency in a diverse society -- The creation of delinquency -- Understanding delinquency: data, correlates, and trends -- Micro-level theories -- Macro-level theories -- Critical theories -- Families in context -- Schools in context -- Peers and gangs in context -- Drugs in context -- Why a separate juvenile justice system? -- Policing and juveniles -- The process of the juvenile court -- Juvenile corrections -- Preventative, rehabilitative, and restorative approaches to delinquency.